CONSEQUENCES OF IRAN’S WITHDRAWAL FROM THE NUCLEAR DEAL FOR EURO-ATLANTIC SECURITY - Чебан, О. Я. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2021)
The circumstances of Iran’s withdrawal from the nuclear deal or the Joint Comprehensive Plan of Action (JCPOA), which was signed between Iran and the six great powers in 2015, were considered. It is indicated that the US withdrawal from the JCPOA in 2018 and US economic sanctions against Iran were the main reasons for Tehran’s phased withdrawal from the nuclear deal. It was noted that the assassinations of two well-known Iranian figures at the beginning and at the end of 2020 – General Qasem Soleimani and nuclear physicist Mohsen Fakhrizadeh provoked Iran to completely abandon the provisions of the JCPOA and to radicalize its nuclear policy. The implications of Iran’s gradual withdrawal from the nuclear deal for the security of Euro-Atlantic structures are analyzed. It has been proven that the risks associated with the development of the Iranian nuclear program were relatively insignificant during 2019. However, these risks began to increase in 2020 and especially at the beginning of 2021. The circumstances of Iran’s decision on possible increasing the uranium enrichment level to 20% and on the probable limiting the access to Iranian nuclear facilities for international inspectors were considered. It is analyzed whether such a decision of Iran can bring this country closer to obtaining nuclear weapons. It is concluded that, most likely, despite the technical capabilities, Iran will not make a political decision to produce an atomic bomb in the near future to avoid its complete isolation. Therefore, the potential nuclear conflict with Iran does not yet threaten to Euro-Atlantic security. Differences in attitudes towards the Iranian nuclear program between the United States and its European NATO allies during Donald Trump’s presidency are traced. The prospects for a change in the American position toward Iran during Joseph Biden’s presidency are assessed. The article analyzes the difficulties that the United States and its allies may face in the course of negotiations with Iran during the presidency of J. Biden. It is indicated that the influential conservative elements in Iran may delay Iran’s return to the nuclear deal in order to bargain for better conditions. It is concluded that the United States and its allies should respond to possible Iranian provocations by economic sanctions rather than by forceful actions, which could lead to an escalation that is dangerous for the Euro-Atlantic security.